Linking Nanoscale Chemical Changes to Bulk Material Properties in IEPM Polymer Composites Subject to Impact Dynamics - Attard, Thomas; He, Li (ACS applied materials & interfaces, 2019)
A synthesizable interfacial epoxy–polyurea-hybridized matrix (IEPM), composed of chemical bonded nanostructures across an interface width ranging between 2 and 50 μm, is a candidate for dialing-in molecular vibrational properties and providing high-impact dynamics resistance to conventional fiber(x)-reinforced epoxy (F/E), engendering an x-hybrid polymeric matrix composite system (x-IEPM-t c). Atomic force microscopy and scanning electron microscopy elucidate the interfacial nanoscale morphology and chemical structure via reaction kinetics of curing epoxy (as a function of time, t c) and fast-reacting (prepolymerized) polyurea. Nano-infrared spectroscopy (nano-IR) spectra, per non-negative matrix factorization analysis, reveal that simultaneous presence of characteristic epoxy and polyurea vibrational modes, within a nanoscale region, along with unique IEPM characteristics and properties following thermomechanical analysis and dynamic mechanical analysis (DMA), indicate chemical bonding, enabling IEPM reaction kinetics, as a function of t c, to control natural bond vibrations and type/distribution of interfacial chemical bonds and physical mixtures, likely due to the bond mechanism between −NCO in polyurea and epoxide and −NH2 in epoxy hardener (corresponding to characteristic absorption peaks in nano-IR results), leading to enhanced IEPM quality (fewer defects/voids). Test results of ballistic-resistant panels, integrated with thin intermediate layers of x-IEPM-b-t c, confirm that lower t c significantly enhances loss modulus (∝ material damping and per DMA) in impact dynamics environments.